Rancang Bangun Sistem Informasi Kepegawaian pada PT. XYZ - Muhammad Maisep; Yogie Prakoso; Ery Hartati (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2016)
This study aims to help PT. XYZ in data processing on data information systems Officer, PT. XYZ is a company engaged in building construction activity. PT. XYZ has a constraint in data processing Personnel acceptance of new, less integrated data storage, calculation of salaries and attendance is less effective, difficulty in performing retrieval leave Personnel as well as in the processing of the warning letter Staff Admin work is still struggling to monitor the warning letters. Thus some of the problems in Pt XYZ information systems need to be built with Iteration methodology. Personnel information system that can cover the deficiencies that exist and present employee data is sistemati in mengolahsistem Personnel data information so that information is obtained quickly and accurately.